2021
DOI: 10.1007/s42452-021-04248-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of quality markers of antiuric acid formula by grey relational analysis

Abstract: Gout has become a global problem, antiuric acid formula (AAF) is a clinical prescription highly effective in reducing uric acid levels. In order to find its quality control standards and contribute to the treatment of gout in the future, we adopted high-performance liquid chromatography and orbitrap liquid chromatography–mass spectrometry to establish fingerprints of 13 batches of AAF. The different batches of AAF were tested the activity of inhibit uric acid by the xanthine oxidase inhibition experiment. Grey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Inhibiting NF-κB activation presents a valid strategy for improving gouty arthritis. Studies (79,80) have demonstrated that calycosin reduces knee joint swelling and neutrophil infiltration in a mouse model of gouty arthritis induced by MSU. Inflammatory markers such as IL-1β, IL-6, IL-10 and TNF-α showed notable decreases in peripheral blood mononuclear cells and THP-1 cells induced by 0.2 mg/ml MSU after a 24-h pre-treatment with calycosin.…”
Section: Immunoinflammatory Disorders and Gouty Arthritismentioning
confidence: 99%
“…Inhibiting NF-κB activation presents a valid strategy for improving gouty arthritis. Studies (79,80) have demonstrated that calycosin reduces knee joint swelling and neutrophil infiltration in a mouse model of gouty arthritis induced by MSU. Inflammatory markers such as IL-1β, IL-6, IL-10 and TNF-α showed notable decreases in peripheral blood mononuclear cells and THP-1 cells induced by 0.2 mg/ml MSU after a 24-h pre-treatment with calycosin.…”
Section: Immunoinflammatory Disorders and Gouty Arthritismentioning
confidence: 99%